2009
DOI: 10.1007/s12217-009-9135-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gravity on Film Boiling Heat Transfer and Rewetting Temperature during Quenching

Abstract: This paper describes the experimental strategy developed to improve the modeling of liquidvapor flows during the chill down of rocket engines by cryogenic fluid in microgravity. A similarity analysis is performed to determine the relevant dimensionless numbers for the design of an experiment similar to engine flows. A literature review on reduced gravity quenching experiments, and on rewetting temperature and film boiling heat transfer shows the lack of validated models for microgravity. Experimental results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The end of the chill down process is usually characterized by a steady pipe wall temperature and the pipe is cooled enough to be rewetted. During chill down, whole boiling curve can be noticed at each pipe location [2]. Many definitions of rewetting temperature is available in literature such as (i) Leidenfrost temperature, minimum film boiling temperature, (ii) quenching temperature from thermocouple observations, and (iii) temperature at which critical heat flux occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The end of the chill down process is usually characterized by a steady pipe wall temperature and the pipe is cooled enough to be rewetted. During chill down, whole boiling curve can be noticed at each pipe location [2]. Many definitions of rewetting temperature is available in literature such as (i) Leidenfrost temperature, minimum film boiling temperature, (ii) quenching temperature from thermocouple observations, and (iii) temperature at which critical heat flux occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Kawanami et al [20] observed higher quench front velocity and heat transfer coefficient in microgravity for vertical quenching of a glass tube with liquid nitrogen. Verthier et al [2] conducted reduced gravity chill down experiments using glass tube and FC72. Results showed decrease in film boiling heat transfer and an increase in chill down temperature under these conditions.…”
Section: Introductionmentioning
confidence: 99%